2023
DOI: 10.1101/2023.01.19.524684
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Immunogenicity and safety in pigs of PHH-1V, a SARS-CoV-2 RBD fusion heterodimer vaccine candidate

Abstract: The continuing high global incidence of COVID-19 and the undervaccinated status of billions of persons strongly motivate the development of a new generation of efficacious vaccines. We have developed an adjuvanted vaccine candidate, PHH-1V, based on a protein comprising the receptor binding domain (RBD) of the Beta variant of SARS-CoV-2 fused in tandem with the equivalent domain of the Alpha variant, with its immunogenicity, safety and efficacy previously demonstrated in mouse models. In the present study, we … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…1.351) and Alpha (B.1.1.7) variants, formulated with an oil-in-water emulsion based on squalene (SQBA) intended for intramuscular administration. [23][24][25] PHH-1V comprises three key mutations of high relevance for previously and currently circulating SARS-CoV-2 variants: K417N, E484K and N501Y. 26 Previous studies revealed that the E484K and N501Y mutations are present in the RBD of the spike protein of Beta, Gamma, and Mu variants; and both the K417N and N501Y mutations present in the PHH-1V antigen are common to the Beta and to the currently predominant Omicron variants.…”
Section: Introductionmentioning
confidence: 99%
“…1.351) and Alpha (B.1.1.7) variants, formulated with an oil-in-water emulsion based on squalene (SQBA) intended for intramuscular administration. [23][24][25] PHH-1V comprises three key mutations of high relevance for previously and currently circulating SARS-CoV-2 variants: K417N, E484K and N501Y. 26 Previous studies revealed that the E484K and N501Y mutations are present in the RBD of the spike protein of Beta, Gamma, and Mu variants; and both the K417N and N501Y mutations present in the PHH-1V antigen are common to the Beta and to the currently predominant Omicron variants.…”
Section: Introductionmentioning
confidence: 99%
“…16 Phase IIb trials demonstrated its efficacy in generating neutralizing antibodies against various SARS-CoV-2 variants, including Omicron XBB. [16][17][18] Long-term analysis revealed sustained immune responses, even in high-risk populations regardless of prior infection or primary vaccine type. 19 Additionally, PHH-1V induces a robust T-cell response.…”
Section: Introductionmentioning
confidence: 99%
“…19 Additionally, PHH-1V induces a robust T-cell response. 17,18 Further, recipients of PHH-1V reported fewer adverse events (AE) than mRNA vaccine recipients, with comparable breakthrough non-severe COVID-19 rates. As a recombinant protein-based vaccine, PHH-1V also may offer advantages, including high productivity, stability, and suitability for immunocompromised individuals, positioning it as a promising candidate in the battle against COVID-19.…”
Section: Introductionmentioning
confidence: 99%